Efferent and Afferent Connections of Neuropeptide Y Neurons in the Nucleus Accumbens of Mice - Yamada, Shunji; van Kooten, Nienke; Mori, Takuma; Taguchi, Katsutoshi; Tsujimura, Atsushi; Tanaka, Masaki (Frontiers in Neuroanatomy, 2021)
Neuropeptide Y (NPY) is a neural peptide distributed widely in the brain and has various functions in each region. We previously reported that NPY neurons in the nucleus accumbens (NAc) are involved in the regulation of anxiety behavior. Anterograde and retrograde tracing studies suggest that neurons in the NAc project to several areas, such as the lateral hypothalamus (LH) and ventral pallidum (VP), and receive afferent projections from the cortex, thalamus, and amygdala. However, the neural connections between accumbal NPY neurons and other brain areas in mice remain unclear. In this study, we sought to clarify these anatomical connections of NPY neurons in the NAc by investigating their neural outputs and inputs. To selectively map NPY neuronal efferents from the NAc, we injected Cre-dependent adeno-associated viruses (AAVs) into the NAc of NPY-Cre mice. This revealed that NAc NPY neurons exclusively projected to the LH. We confirmed this by injecting cholera toxin b subunit (CTb), a retrograde tracer, into the LH and found that approximately 7–10% of NPY neurons in the NAc were double-labeled for mCherry and CTb. Moreover, retrograde tracing using recombinant rabies virus (rRABV) also identified NAc NPY projections to the LH. Finally, we investigated monosynaptic input to the NPY neurons in the NAc using rRABV. We found that NPY neurons in the NAc received direct synaptic connections from the midline thalamic nuclei and posterior basomedial amygdala. These findings provide new insight into the neural networks of accumbal NPY neurons and should assist in elucidating their functional roles.